2011
DOI: 10.4049/jimmunol.1002321
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3-Mediated Suppression of CD95L Expression Confers Resistance to Activation-Induced Cell Death in Regulatory T Cells

Abstract: CD4+CD25++Foxp3+ regulatory T cells (Tregs) control self-reactive cells to maintain peripheral tolerance. Treg homeostasis has to be controlled tightly to ensure balanced Treg-mediated suppression. One mechanism that regulates the CD4+ T cell pool is activation-induced cell death (AICD). This is mimicked in vitro by TCR restimulation-induced expression of the death ligand CD95L (FasL/APO-1L/CD178) in expanded T cells. These cells express the death receptor CD95 (Fas/APO-1), and binding of CD95L to CD95 results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 43 publications
6
49
0
Order By: Relevance
“…The most significantly different markers were CD95, CCR4, and CD45RO. [36][37][38] The identified Treg subpopulations were compared with established Treg subpopulation definitions. 23 Although Tregs A and B overlap with Treg subpopulations I and II, respectively, our approach demarcates those Treg III cells that are closer to Tregs and combine them with subpopulation A or B based on their phenotype and eliminate cells that are closer to T con and less likely to be regulatory.…”
Section: Discussionmentioning
confidence: 99%
“…The most significantly different markers were CD95, CCR4, and CD45RO. [36][37][38] The identified Treg subpopulations were compared with established Treg subpopulation definitions. 23 Although Tregs A and B overlap with Treg subpopulations I and II, respectively, our approach demarcates those Treg III cells that are closer to Tregs and combine them with subpopulation A or B based on their phenotype and eliminate cells that are closer to T con and less likely to be regulatory.…”
Section: Discussionmentioning
confidence: 99%
“…Fas/FasL also induced apoptosis in Tregs (128). The Fas/FasL pathway alone cannot induce immune tolerance (129).…”
Section: T Effectors Die Of Activation-induced Cell Deathmentioning
confidence: 99%
“…Next, to further characterize the Treg-of-B1a cells, we used a number of molecules reported to be associated with the functions of Treg cells. [22][23][24][25][26][27][28][29][30] We found that Treg-of-B1a cells expressed a series of surface molecules, including ICOS, PD-1, GITR, OX40, IL-10R and TNFR2 (Figure 3b). Among them, ICOS, GITR, IL-10R and PD-1 were expressed at higher levels Therefore, B-1a cells are the major IL-10-producing cell population present in the steady-state peritoneal cavity, and they spontaneously produce IL-10 without any stimulation.…”
Section: B-1a Cells Convert Naive Cd4 1 T Cells Into Foxp3 2 Treg Cellsmentioning
confidence: 99%